OC-074 BILAYERED RETICULAR AND LAMINAR POLYPROPYLENE MESH AS A USEFUL TEMPORARY ABDOMINAL CLOSURE FOR THE MANAGEMENT OF THE OPEN ABDOMEN. (13th October 2022) - Lopez Monclus, J; Muñoz Rodriguez, J; Roman Garcia De Leon, L; Polaino Moreno, V; Suarez Sanchez, M; Gil Cidoncha, L; Martin Rodrigo, P; Lucena De La Poza, J L; Robin, A; Blazquez Hernando, L; Garcia Ureña, M A
Abstract: Aim: To demonstrate the utility of a bilayered reticular and laminar polypropylene (PLP) mesh as a temporary abdominal closure device for the management of the open abdomen. Patients And Methods: Prospective multicentric study including consecutive patients with open abdomen of any etiology. A bilayerede PLP mesh is used as temporary abdominal closure. The mesh has a 30×40 cm laminar PLP intraperitoneal layer that is fully deployed covering the viscera, and a 30x 40 cm large pore PLP layer that is trimmed to the size of the defect and sutured to the border of the fascia. Depending on the evolution time and the clinical situation of the patient, successive plicatures of the reticular PLP are performed to reduce the fascial defect. At the end, the mesh is explanted, and a complete fascial closure is attempted. Results: Eighteen patients were included. Etiologies of the open abdomen were vascular (22%), trauma (28%) and sepsis (50%). There were 72% female patients, mean age of 60 years (range 19–81). Four patients died in the first 72 hours due to complications of their pathology. The other 14 patients survived, with a mean time of open abdomen of 15 days (range 1–43). In all cases a total fascial closure was achieved, with absence of adhesions between the visceral and the parietal peritoneum. No complications related with the mesh took place during the follow up Conclusion: Temporary abdominal closure with a bilayered reticular and laminar polypropylene mesh is efficient and safe, with a 100% rate of fascial closure